Global, regional, and national burdens of traumatic brain injury from 1990 to 2021 - Yan, Junqing; Wang, Chao; Sun, Bangqing (Frontiers in Public Health, 2025)
BackgroundOf all the injuries on a global scale, traumatic brain injury (TBI) has the most serious consequences for the individual. Depending on its severity, it can be classified as minor, moderate, or severe, but even minor TBI can sometimes still cause severe functional deficits. This study seeks to assess the latest burden of TBI and analyze their differences in terms of country, age, sex, and cause.MethodsBased on the Global Burden of Diseases database, the incidence, years lived with disability (YLDs), and causes of total head injuries, minor TBI, and moderate/severe TBI from 1990 to 2021 were analyzed separately by sex, age group, and region.ResultsIn 2021, there were 20,837,465 [95% uncertainty interval (UI): 18,128,306–23,839,393] new cases of TBI worldwide, with an age-standardized incidence of 259 cases per 100,000 population (95% UI: 226–296). From 1990 to 2021, there was a decline in global age-standardized incidence (estimated annual percentage change: −0.11, 95% UI: −0.18% to −0.04%). In 2021, countries with higher rates will be mainly in Central and Eastern Europe and the Middle East. In 2021, the global incidence of TBI in all age groups was higher in men than in women. Falls are the leading cause for most age groups in most areas.DiscussionTBI still accounts for a significant portion of the global injury burden in 2021, but differences do exist between countries. This study introduced the possibility of TBI with different degrees and the trend of injury causes in different age groups and regions from 1990 to 2021, providing a basis for further research on injury causes in different regions and formulating corresponding policies and protection measures in the future.